Differences in the Likelihood of Acyclovir Resistance-Associated Mutations in the Thymidine Kinase Genes of Herpes Simplex Virus 1 and Varicella-Zoster Virus - Fujii, Hikaru; Harada, Shizuko; Yoshikawa, Tomoki; Yamada, Souichi; Omura, Natsumi; Shibamura, Miho; Inagaki, Takuya; Kato, Hirofumi; Fukushi, Shuetsu; Saijo, Masayuki (Antimicrobial agents and chemotherapy, 2019)
Acyclovir (ACV) resistance-associated mutations in two recombinant herpes simplex virus 1 (HSV-1) clones were compared. Recombinant HSV-1 lacking its thymidine kinase (TK) and expressing varicella-zoster virus (VZV) TK ectopically had no mutations in the VZV TK gene. Acyclovir (ACV) resistance-associated mutations in two recombinant herpes simplex virus 1 (HSV-1) clones were compared. Recombinant HSV-1 lacking its thymidine kinase (TK) and expressing varicella-zoster virus (VZV) TK ectopically had no mutations in the VZV TK gene. In contrast, recombinant HSV-1 expressing HSV-1 TK ectopically harbored mutations in the HSV-1 TK gene. These results suggest that the relatively low frequency of ACV-resistant VZV is a consequence of the characteristics of the TK gene.